Pertumbuhan dan Hasil Tiga Varietas Tomat Pada Aplikasi Pupuk Organik Cair - Rini Suryani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2017)
This study aimed to obtain growth and development of three varieties of tomatoes and determine the best application of liquid organic fertilizer. The experimental design used was Split Plot Design with three replications. As the main plots are varieties of tomato hybrids that include Betavila F1, Marta and Timoty. As subplot is application of liquid fertilizer with application of giving by leaf (LD), through root (LA), and control. The result showed that mean application of liquid organic fertilizer (POC) and tomato varieties increased growth and yield on all observed variables such as plant height, flowering age, harvest age, number of fruit and fruit weight on tomato plants. While the interaction between application of organic liquid fertilizer and varieties have significant effect on plant height variable, flowering age, harvest age, but no significant effect on fruit weight. Appearance of vegetative growth and generative varieties of Marta gives the best result, however for the age of flowering and the age of the fastest harvest seen in varieties of Timoty.